Severity scores and their associated factors among orally poisoned toddlers: a cross sectional single poison center study. Issue 1 (December 2016) - Alanazi, Menyfah; Al-Jeraisy, Majed; Salam, Mahmoud
Abstract Background One of the most unfortunate events toddlers may encounter during their early years of curiosity and experimentation is substance poisoning. The aim of the study was to evaluate the poison severity score and its associated factors among toddlers with orally ingested substances at a pediatrics emergency department (ED), central Saudi Arabia. Methods A cross-sectional, poisoning report review between 2009&2011 was conducted. Exposures were patient characteristics (sex, age, body mass index, medical history) and incident characteristics (substance type, amount, form, witnessed or not, home remedy, arrival time to ED). Outcome was Poison Severity Score (PSS) that rates signs/symptoms of 11 body aspects on scale 0–4 (none, minor, moderate, severe, fatal). Inclusion criteria: age (1–3 years), previously healthy and oral exposure route. Bivariate analysis and multi-linear regression were conducted. Significance at p < 0.05. Results Eligible cases were 165/315(52 %). Males (58 %) and females (42 %) had normal BMI (70 %). Substances ingested were medications (60 %) and chemicals (40 %). Almost 85 % were witnessed incidents and 27 % received a home remedy (water, juices, dairy products, salt/sugar solutes, and/or manually induced vomiting). Delayed arrival (≥1 hour) was observed in 57 %. Composite mean PSS of total was (0.16 ± 0.21), and was highest at the gastrointestinal (GI) aspect (0.39 ± 0.63), metabolic balance (0.35 ± 0.60), and respiratory aspect (0.30 ± 0.61). Significantly associated factors with higher severity scores were: home remedies at the composite mean PSS (adj.p = 0.048), chemical poisoning at two aspects respiratory (adj.p = 0.047) and muscular (adj.p = 0.009) compared to medication poisoning. Unwitnessed incidents at the muscular aspect (adj.p = 0.026) compared to witnessed incidents; delayed arrival time to ED at three aspects GI (adj.p = 0.001), nervous system (adj.p = 0.014) and kidney (adj.p < 0.001). Conclusions Parents are not recommended to provide any home remedy to their orally poisoned toddlers, but rather directly visit the ED. Physicians are expected to observe more severe clinical outcomes among toddlers with chemical poisoning, unwitnessed incidents, and delayed arrival times especially at the respiratory, GI, muscular, nervous and kidney aspects.